Hypertensive disorders in pregnancy and risk of asthma in offspring: a systematic review and meta-analysis - Ping Li; Tao Xiong; Yong Hu (BMJ Open)
Objectives The association between hypertensive disorders in pregnancy (HDP) and an increased risk of asthma in offspring remains controversial. No systematic review of this topic has been performed. The aim of this systematic review was to summarise the available evidence regarding the association between HDP and the risk of asthma in offspring.Design Systematic review and meta-analysis.Methods On the basis of a prepared protocol, a systematic search of PubMed, EMBASE, the Cochrane Library and Web of Science was performed using a detailed search strategy from the database inception to 17 January 2020. Cohort, case–control and cross-sectional studies published in English reporting the diagnoses of maternal HDP and asthma in offspring were included. The Meta-analysis of Observational Studies in Epidemiology guidelines were followed throughout the study. The estimated pooled ORs of HDP and asthma in offspring were calculated from the studies, and the meta-analysis was performed using random-effects models.Results Ten cohort studies involving a total of 6 270 430 participants were included. According to the Newcastle-Ottawa Scale, the overall methodological quality was good since 8 studies were of high quality and 2 studies were of moderate quality. After controlling for potential confounders, HDP was associated with a possible increased risk of asthma in offspring, with a pooled adjusted OR (aOR) of 1.19 (95% CI 1.12 to 1.26). The subgroup analyses according to HDP subgroups, sibling design, study quality, study location, offspring ages, singleton status, exposure assessment, outcome assessment and adjusted factors showed similar results.Conclusions Exposure to HDP may be associated with an increased risk of asthma in offspring. Further research is needed to verify the results and determine whether the observed relationship is causal.PROSPERO registration number CRD42020148250.